Effect of cooking food in iron pot and with iron ingot on increase in hemoglobin level and iron content of the food - Sharma, Shally; Khandelwal, Ritika; Yadav, Kapil; Ramaswamy, Gomathi; Vohra, Kashish (Nepal Journal of Epidemiology, 2021)
In developing countries there is a need for simple and cost-effective strategies to reduce the prevalence of iron deficiency anemia. The objective of the current systematic review is to summarize how cooking food in iron pots or iron ingots can increase the blood hemoglobin level and iron content of the food. Literature search was conducted using databases namely PubMed, Google Scholar, Medline-Ovid, IndMed, Cochrane library, World Health Organization bulletin and by cross-referencing articles. Thirteen researches were found to be suitable for inclusion in this systematic review. Four studies reported significant increase in blood hemoglobin levels while others reported only a minor increase. Significant improvement in amount of iron in food and iron bioavailability was also observed when food was cooked using iron pot or ingots. This can be used as a strategy for reduction of iron deficiency anemia. However, more research is required to understand the efficacy of this approach.